2019
DOI: 10.1016/j.erss.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Energy insecurity and its ill health effects: A community perspective on the energy-health nexus in New York City

Abstract: This study examines the effects of a novel construct -energy insecurity -on adverse health in a community-based sample in New York City. Using a 2015 cross-sectional study of 2,494 households in Washington Heights, we described the socio-demographic characteristics of energy insecure households and examined the association between energy insecurity and health outcomes using logistic regression models. Twenty-seven percent of participants were energy insecure. Racial/ethnic minorities, households with children,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Across all income levels, Black families still maintained the highest rates of energy insecurity (60). In the Washington Heights neighborhood in New York City, energy-insecure households were more likely to be black and Hispanic/Latino, low-income, and have less education (64). In Detroit, a study found that African-American households were twice as likely to be behind on utility payments and three times more likely to suffer from arrearage or shut-offs than white households (65).…”
Section: Racementioning
confidence: 99%
See 2 more Smart Citations
“…Across all income levels, Black families still maintained the highest rates of energy insecurity (60). In the Washington Heights neighborhood in New York City, energy-insecure households were more likely to be black and Hispanic/Latino, low-income, and have less education (64). In Detroit, a study found that African-American households were twice as likely to be behind on utility payments and three times more likely to suffer from arrearage or shut-offs than white households (65).…”
Section: Racementioning
confidence: 99%
“…Gentrifying or newer residents are less likely to experience energy insecurity or have an energy inefficient home compared to longer-term residents who live in older households in the area (97). Long-term residents of Washington Heights in New York City, for example, are Dominican immigrants and African Americans, and they suffer far more energy insecurity than new neighborhood residents (64).…”
Section: Socioeconomic Status Race and Placementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that sustainable development of communities is affected by the well-being of its inhabitants which are often predetermined by the type of energy used [19] and the availability of electrified health facilities [20]. For example, in the studies of Hernández and Siegel [21] and Zhang et al [22], it has been determined that energy poverty and insecurity has negative impact on people's health and community development [23]. In many countries in sub-Saharan Africa, community-based health facilities are either underelectrified or do not have access to electricity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Further, well-being could probably be maximized at levels of energy consumption much lower than that found in wealthy nations like the USA and Western Europe [9,20,47,48]. Increasingly, research is pointing to energy security as a key variable in the relationship between energy and well-being [24,25]. In this paper, we ask how worries about energy security influence self-rated health.…”
Section: Introductionmentioning
confidence: 99%